Evaluation of an Interprofessional Academic-Practice Partnership in End of Life Care - Katie F Leslie; M. Kate Probst; Taylor L Hawkins (University of Minnesota Libraries Publishing, 2021)
Introduction: The purpose of this mixed-methods study was to evaluate an interprofessional academic-practice partnership in end of life care by examining patient medication outcomes, the contributions of student pharmacists and a pharmacy preceptor to care teams, and student learning experiences. Methods: Retrospective chart review assessed polypharmacy differences in hospice patients with a primary terminal diagnosis of non-Alzheimer's dementia between two patient groups; Group 1 managed on interprofessional care teams within the pharmacy partnership, and Group 2, managed on teams without a pharmacist. Team members who interacted with student pharmacists and the pharmacy preceptor participated in semi-structured key informant interviews to document perceptions of pharmacy contributions to care teams and the organization. At the end of their APPE, students completed reflective writings regarding their learning.   Results: Patients in Group 1 were on statistically significant fewer medications than Group 2 at both week 4 and weeks 7-12 following admission.  Five conceptual themes emerged from interviews: pharmacists as team medication experts, improved patient outcomes, interprofessional collaboration, patient/caregiver trust in medication regimens, and desire for sustainability. Student reflections included the following learning themes: teamwork, respect, value, and patient-centered care. Conclusions: The addition of a pharmacist on interprofessional care teams decreased the average number of medications in the non-Alzheimer's end of life patient population. Team members identified value-added contributions of student pharmacists and the pharmacy preceptor that enhanced team efficiency and patient care. Student pharmacists recognized these contributions and the experience served as an exemplar of interprofessional practice.